Pelatihan Jurnalistik bagi Pemuda Desa Randupitu sebagai Upaya Penguatan Literasi Media Berbasis Komunitas - Sholihat Jamil, Amidatus; Zenmira, Kharisma Nanda; Widya Astuti, Eka Rini; Machfudi Zulkif, Senjaya (Humanist Journal, 2024)
In today's digital society, journalistic skills are an important asset in building a critical and information-aware community. This community service activity aims to improve the journalistic capacity of youth in Randupitu Village, Gempol District, Pasuruan Regency. Through structured journalism training and a participatory approach, this program equips participants with news writing skills, understanding journalistic ethics, and the use of digital tools in the production and distribution of information. This activity was carried out by a team of lecturers from across study programs at Nahdlatul Ulama University, Pasuruan, in collaboration with the KIM Gempar Randupitu community. The results of the program showed an increase in participants' understanding of journalistic techniques, as well as practical skills that began to be applied in the form of community digital content. This program is a model for youth involvement in strengthening inclusive and sustainable community-based media literacy.